ConcepÃÃes e vivÃncias sobre o Programa de SaÃde da FamÃlia em Fortaleza - Alessandra Pereira Viana (2004)
This research turns on the Program of Health of Family (PSF) in Fortaleza, looks for to understand, through the study of the clarifying models constructed by the medical professionals and nurses who in it act, as processed its implantation, organization and execution. It is a study of qualitative nature, that used the half- structure interview to identify perceptions, sadness and feelings of constructed satisfaction and not satisfaction through practical its of the PSF in the city of Fortaleza. Fourteen professionals had participated of the research, being seven nurses and seven doctors who act or had acted in the city during its implantation. The study he disclosed that the implantation of the Program of Health of the Family in the city of Fortaleza was marked by a series of events, between them if they detach: the exit of the professionals who acted in the old model and the arrival of the teams of health of the family; scarcity of human resources and substances; reduction of the number of qualifications and the interference partisan politics in the work process. All these had difficulty lements for the implantation process, had contributed so that it had to the eyes of the professionals interviewed, a distortion of the objectives of the PSF during its implantation and implementation. When questioned on its professional satisfaction the professionals they disclose negative and positive dimensions of practical its. Thus, the interviewed professionals live a paradoxical relation, enter the pleasure to exert practical its and the frustration generated for the informality and not the recognition of the Health of the Family, while specialty. Keywords: Family Health Program. Health Policy. Program Evaluation